Analisis Persepsi Konsumen tentang Brand Association Produk Minuman Bervitamin You-C 1000 - Adila Solida; Fahrizal Fahrizal; Ardiyansyah Ardiyansyah (Ekonomis: Journal of Economics and Business, 2022)
A brand that is widely known to the public is a very important asset for the company. Therefore, maintaining and increasing brand equity is a serious and challenging job, because what is faced is customer expectations. This study aims to describe consumer perceptions of the brand association of beverage products containing vitamin You-C 1000. This type of research is a descriptive survey method. The population of this study are consumers or buyers of vitamin You-C 1000 beverage products in Indomaret Broni, Jambi City. The sample was determined by accidental sampling technique, so 38 respondents were obtained in Indomaret Broni Jambi City from June 2022 to July 2022. Data collection techniques were by distributing questionnaires and literature studies. The data processing technique used is data processing with the help of SPSS version 26 software and using a Likert scale. The results of this study indicate that consumer perceptions of brand associations can be seen from several dimensions, namely: the dimension of assurance, the dimension of personal identification, the dimension of social identification, the dimension of status, the dimension of willingness to accept brand extension, and the dimension of willingness to recommend a brand. The findings of the analysis on all these dimensions state that consumer perceptions of the brand association of beverage products containing vitamin You-C 1000 in Indomaret Broni, Jambi City are perceived positively.